2020
DOI: 10.1055/s-0039-1700979
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Bilateral Total Knee Arthroplasty Becomes Safer after Institution of Optimal Perioperative Management: A Longitudinal Cohort Study

Abstract: Simultaneous bilateral total knee arthroplasty (SBTKA) increases the rates of procedure-related complications and mortality compared with unilateral TKA. There are no well-defined guidelines for selecting patients to avoid mortality and proposing an upgrade treatment to decrease complication rates. This study aimed to evaluate whether optimal perioperative management could improve the safety of SBTKA. From 2005 to 2017, 1,166 cases of SBTKA were identified from 14,209 TKA procedures. We retrospectively examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Recent studies suggest that careful selection of patients can reduce complications to similar rates. 7,11,15,16 For instance, patients who are older and/or have concomitant cardiopulmonary conditions, who are morbidly obese (BMI >40 kg/m 2 ) or have higher ASA scores should be treated with caution, due to a relatively higher risk of surgical complications. 8,[17][18][19] Interestingly, SiTKA is considered a safe procedure in patients with conditions such as rheumatoid arthritis, end-stage hemophilic arthropathy, and moderate obesity (BMI 30-35 kg/m 2 ), all conditions previously considered risk factors for postoperative complications in unilateral TKA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggest that careful selection of patients can reduce complications to similar rates. 7,11,15,16 For instance, patients who are older and/or have concomitant cardiopulmonary conditions, who are morbidly obese (BMI >40 kg/m 2 ) or have higher ASA scores should be treated with caution, due to a relatively higher risk of surgical complications. 8,[17][18][19] Interestingly, SiTKA is considered a safe procedure in patients with conditions such as rheumatoid arthritis, end-stage hemophilic arthropathy, and moderate obesity (BMI 30-35 kg/m 2 ), all conditions previously considered risk factors for postoperative complications in unilateral TKA.…”
Section: Discussionmentioning
confidence: 99%
“…26 The use of intraoperative tranexamic acid via the intravenous or intraarticular route can also effectively reduce blood loss. 16 At our institution, based on preference, the surgeon may use one or more of these methods. Therefore, although SiTKA involves substantial blood loss and higher rates of transfusion, the overall rate of adverse reactions is minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that careful selection of patients can reduce complications to similar rates. [3,11,27,28] For instance, patients that are older and/or have concomitant cardiopulmonary conditions, morbidly obese (BMI>40 kg/m 2 ), and higher ASA scores should be treated with caution due to a relatively higher risk for surgical complications. [7,9,10,24] Interestingly, SiTKA is considered to be a safe procedure in patients with conditions such as rheumatoid arthritis, end-stage hemophilic arthropathy, and moderate obesity (BMI 30-35 kg/m 2 ) which were previously thought as risk factors for postoperative complications in unilateral TKA.…”
Section: Discussionmentioning
confidence: 99%
“…[22] Furthermore, the use of intraoperative tranexamic acid via intravenous or intraarticular route have been also shown to effectively reduce blood loss. [3] In our institution, one or a combination of the above methods are currently in practice and is dependent on the surgeon's preference. Therefore, although there is substantial blood loss and higher rates for transfusion, the overall rate of adverse reactions is minimal.…”
Section: Discussionmentioning
confidence: 99%